Diversity of ectomycorrhizal fungi associated with Quercus petraea in the national park Fruška gora in the Republic of Serbia : Raznolikost ektomikoriznih gljiva na hrastu kitnjaku (Quercus petraea) u Nacionalnom parku Fruška gora u Republici Srbiji - Milović, Marina (Array, 2021)
Although sessile oak is one of the most important deciduous forest tree species in Europe, data on the diversity of ectomycorrhizal (ECM) fungi on sessile oaks in the Republic of Serbia are scarce. The aim of this study was to provide the first insight into the diversity of ECM fungi on sessile oak in Serbia. Two sites Info center and Brankovac, located in National Park Fruška gora were chosen. ECM fungi were identified combining morphological and anatomical characterization with molecular analysis of nuclear rDNA internal transcribed spacer (ITS) region. All vital ECM root tips were counted, diversity indices were calculated, and ECM fungi were classified into the exploration types. The granulometric and chemical composition of soil were analyzed as well. At both sites, 26 different ECM fungal taxa were recorded in total, 17 taxa were observed at the site Info center and 12 taxa at Brankovac. ECM communities consisted of a few abundant taxa and a larger number of rare taxa. Lactarius quietus, Cenococcum geophilum, and Tomentella sublilacina were recorded at both sites. High abundance of contact and short-distance exploration types recorded in studied stands suggests that soils are sufficiently rich in total nitrogen and organic matter. Values of diversity indices recorded in studied sessile oak stands from Fruška gora were lower in comparison to those obtained in stands of different oak species across Europe which is likely induced by drought. To get a more thorough insight into the diversity of ECM fungi on sessile oak, research should be continued at more sites and seasonal dynamics should be included.